Sertifikasi Guru Sebagai Syarat Guru Profesional - Sari, Renika Indah; Said, Rosdiana; Achruh, Andi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aimed to find out how the role of teacher certification in improving the ability of educators in Mas Yapib Tompobulu Jeneponto. Teacher certification becomes imperative for teachers to demonstrate professionalism as an educator or teaching personnel especially in Indonesia and this certification can promote teachers’ well-being. This type of research is qualitative research with field approach (Field Research) i.e. direct research to the location to obtain and collect data. The methodology in this study uses Data collection techniques are drawn from interviews, observation and documentation. Data analysis techniques using Data reduction, data presentation and drawing conclusions. The results of the study show that certification is used as a measure of a professional, kind, and competent teacher. Teachers who have done certification will strive to develop the skills they have. This teacher certification is crucially done to demonstrate teachers’ professionalism as teachers and educators. The implementation of the results of this study is to know the importance of dissemination of important related information as well as implementation of certification should be regularly done even to the corners of the area so that all teachers can receive information and follow certification to become professional and competent teachers